Reasons for cannabis use among youths at ultra high risk for psychosis. Issue 3 (26th November 2013) - Gill, Kelly E.; Poe, Lucy; Azimov, Neyra; Ben‐David, Shelly; Vadhan, Nehal P.; Girgis, Ragy; Moore, Holly; Cressman, Victoria; Corcoran, Cheryl M.
Abstract: Aim: Cannabis use is prevalent in schizophrenia and its risk states, despite its association with anxiety and positive symptoms. While schizophrenia patients report using cannabis for mood enhancement and social motives, it is not known what motivates clinical high risk (CHR) patients to use cannabis. Methods: Among 102 CHR patients, 24 (23%) endorsed cannabis use, and were queried as to reasons for use, using a scale previously administered in schizophrenia patients. We hypothesized a primary motivation for mood enhancement related to anhedonia. We evaluated the 'self‐medication' hypothesis by examining if motivation for symptom relief was associated with concurrent severity of symptoms. Results: The rank order of reasons for use in CHR patients was similar to that previously reported by schizophrenia patients, with mood enhancement and social motives as primary reasons for use, and the motivation to use cannabis for symptom relief comparatively less common. Motivation for mood enhancement had a trend association with anhedonia. Motivation for symptom relief was entirely unrelated to concurrent severity of positive and anxiety symptoms. Conclusion: As in schizophrenia, CHR patients primarily use cannabis for mood enhancement, especially in the context of decreased motivation to seek pleasure otherwise. Negative symptoms may drive cannabis use in schizophrenia and its risk states, which may exacerbate positive symptoms. By contrast, CHR patients do not report using cannabis to 'self‐medicate' emergent positive symptoms. The understanding of motives for cannabis use among CHR patients may be informative for treatments aimed at reducing use, such as motivational interviewing.